Vienna view from the Biber Bastion - Finden, Edward Francis, 1791-1857 (engraver):::Creator::::::::::::; Batty, Robert, 1789-1848 (artist):::Contributor:::::::::::: (Rodwell & Martin; London; United Kingdom)
Engraving of Vienna viewed from the Biber bastion